THE USE OF CROSSWORD PUZZLE GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT SMP NEGERI 2 TONDANO - Klise, Hiyashinta Ampasenan; Pelenkahu, Noldy; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research was proved that the use of Crossword Puzzle game in teaching vocabulary can improve students’ vocabulary or not. This research was used quantitative research through pre-experimental research with one group pre-test and post-test design. Pre-test was a test which is given to the students before treatment. And post-test was a test which is given after treatment. There are 2 tests: T1 is the pre-test and T2 is post-test. X is used symbolize the treatment. This research was conducted at students on the 7th grade SMP Negeri 2 Tondano. The subject will take from one class of junior high school. This school was used K-13 as their curriculum. There are several classes of the second grade students at SMP Negeri 2 tondano and one class will chose as the subject of study. The result of the data analysis showed that from 20 students who had took a part of pre-test obtained 70 as the higher scores achieved by seven student while the lowest score 50 obtained by three students. After treatment four student acquired 100 as perfect scores and student acquired 70 as imperfect score. Table 6 showed that the mean score ( ) of pre-test (T1) was 62 and Standard Deviation (S12 = 65) and the mean score ( ) of post-test (T2) was 85, 5 with Standard Deviation (S22= 90) in post-test. In this study the data of the pre-test were compared to the data of the post-test therefore it should be said that the result of the post-test was better than the pre-test. The result of pre-test showed that the students’ vocabulary achievement was low before applying Crossword Puzzle game because they did not really understand the meaning of vocabulary. So, this research proved that the Crossword Puzzle game is an effective in teaching vocabulary in order to improve student’s vocabulary skill.